PERBANDINGAN EFEKTIVITAS EKSTRAK DAUN BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) 25% DAN 50% DIBANDINGKAN OBAT TRIAMCINOLONE ACETONIDE TERHADAP PENYEMBUHAN RECURRENT APHTHOUS STOMATITIS (RAS) MINOR - Ni Nyoman Gemini Sari; Kemala Dewi, Intan; Trimulyani , Komang Ayudita (Interdental: Jurnal Kedokteran Gigi, 2020)
Recurrent Aphthous Stomatitis (RAS) is an inflammation of the soft tissues of the mouth characterized by recurrent ulcers without symptoms of other diseases. Clinically, RAS is characterized by painful recurrent ulcerations of the oral mucosa that appear recurrently in single or multiple numbers and have a red halo appearance that usually appears on the lip, cheek, lateral, and ventral mucosa of the tongue in the oral cavity. Triamcinolone acetonide is a prednisolone derivative and is considered an intermediate glucocorticoid. It is effective in reducing the signs and symptoms of many conditions of inflammation of the mouth, including RAS. Binahong contains active compounds of flavonoids, alkaloids, terpenoids, and saponins which have an antibacterial effect in inhibiting the growth of Streptococcus mutans and Staphylococcus aureus bacteria. so Binahong leaf extract can be used as an alternative natural treatment for minor RAS. This research compared the effectivity of extracts leaves Binahong (Anredera cordifolia (Ten.) Steenis) concentrations of 25%, 50% with Triamcinolone Acetonide in healing Recurrent aphthous stomatitis (RAS) minor. The research was pretest-posttest control group design, 30 samples divided into 3 treatment groups, where the treatment group I used Triamcinolone acetonide, treatment group II used 25% binahong leaf extract, and treatment group III used 50% Binahong leaf extract. Data were analyzed with a parametric statistical test of paired sample T-test and showed that there was a significant decrease in RAS diameter in groups I, II, and III (p <0.05). The mean difference of RAS diameter between-group in order 2.7mm for the first treatment group, in the second treatment group, was 1.3mm and 2.2mm for the third treatment group. Analysis with Oneway ANOVA showed that after the treatment was given to the three groups, there was a significant average difference of the minor RAS diameter decrease (p <0.05). The results showed that Triamcinolone acetonide was more effective in accelerating the healing of minor RAS than 25% and 50% binahong leaf extract.